Empirical model of the wake-induced lift force on a cylinder with low mass ratio. (November 2021) - Song, Hong; Huang, Weiping; Fu, Xuepeng; Yan, Haoran; Chang, Shuang
Abstract: The vortex-induced vibrations (VIV) of two flexible circular cylinders in a tandem configuration were studied numerically for spacing ratios ranging from 6 to 18 and the reduced velocities ranging from 2.35 to 12.59. The VIV response amplitude, response frequency, fluid force, pressure distribution and vortex structure of the tandem cylinders with different spacing ratios under different reduced velocities were compared. The results indicate that there is a great difference between the lift forces on the downstream and upstream cylinders. The lift coefficient of the downstream cylinder undergoing the wake-induced vibrations (WIV) is larger than that of the upstream cylinder, and the dominant frequency curves of the lift coefficients of the upstream and downstream cylinders separate. It can be found that the length and intensity of the wake are quite different under different reduced velocities and spacing ratios, and the reattachment positions between the wake and the downstream cylinder are different, which leads to a great change in the flow around the downstream cylinder and have a great effect on the wake-induced lift force on the downstream cylinder. Considering these factors, an empirical model for the wake-induced lift force on a cylinder with low mass ratio was proposed and verified. Highlights: The upstream cylinder wake has different effects on wake mode, vibration frequency, amplitude, and lift force of the downstream cylinder. Both the reduced velocity and the spacing ratio have a great effect on the wake-induced lift force on the downstream cylinder. An empirical model for the wake-induced lift force on a cylinder with low mass ratio was proposed and verified. The WIV of the downstream cylinder can be simulated by the lift force empirical model combined with the motion equations.